2021
DOI: 10.31234/osf.io/9aqbj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imagination, anxiety, and loneliness during the COVID-19 pandemic.

Abstract: Imagination is relevant in many aspects of our lives, and has been associated with creativity and overall cognitive development, yet imagination may also have a dark side. In two studies we examined the link between imagination, anxiety, and loneliness during the COVID-19 pandemic. US college students (N = 101, Study 1) and participants from an international community sample (N = 61, Study 2) were tested around the time that rates of COVID-19 cases were escalating. Across both samples, we found that spending m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Many countries applied (and still apply) similar measures to limit the spread of the virus. These constraints imply a restriction of movement, the need to adapt working methods (remote working, partial unemployment), a modification of daily life within households (e.g., management of children, protection of vulnerable people, living conditions), and a decreased wellbeing (linked to health issues, restrictions of activities and social interactions, or economic consequences) with elements of distress, loneliness, and anxiety [1][2][3][4][5] . Paradoxically, during this period, general and social media have reported that individuals and businesses seemed to show great adaptability to face the situation by finding innovative solutions as well as creative behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many countries applied (and still apply) similar measures to limit the spread of the virus. These constraints imply a restriction of movement, the need to adapt working methods (remote working, partial unemployment), a modification of daily life within households (e.g., management of children, protection of vulnerable people, living conditions), and a decreased wellbeing (linked to health issues, restrictions of activities and social interactions, or economic consequences) with elements of distress, loneliness, and anxiety [1][2][3][4][5] . Paradoxically, during this period, general and social media have reported that individuals and businesses seemed to show great adaptability to face the situation by finding innovative solutions as well as creative behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The situation related to COVID-19 likely has a major impact on many if not all the creativity dimensions or factors described above, by affecting our emotions, motivations, and wellbeing, modifying our environment, our lifestyle, and availability, but also by modifying the standards and incentives of our society during this period, opening a new framework of thought 30,31 . Several studies reported how the pandemic and lockdown had increased psychological distress, mood disorders, loneliness, and anxiety [1][2][3][4][5] , with a potential negative impact on creativity. Nevertheless, the few existing scientific studies that explored creativity during the COVID-19 pandemic have indeed suggested that the lockdown period facilitated everyday creativity 32,33 or that creative abilities could help people dealing with the situation and improve their wellbeing 3,34,35 .…”
Section: Introductionmentioning
confidence: 99%
“…The situation related to COVID-19 likely had a major impact on many if not all the creativity dimensions or factors described above, by affecting our emotions, motivations, and wellbeing ( Bu et al, 2020 ; Li et al, 2020 ; Michinov and Michinov, 2020 ; Roma et al, 2020 ; Zabelina et al, 2021 ), modifying our environment, our lifestyle, and availability, but also the standards and incentives of our society during this period, opening a new framework of thought ( Kapoor and Kaufman, 2020 ; Beghetto, 2021 ). The few existing scientific studies that explored creativity during the COVID-19 pandemic have indeed suggested that the lockdown period facilitated everyday creativity ( Karwowski et al, 2021 ; Mercier et al, 2021 ) or that creative abilities could help people dealing with the situation and improve their wellbeing ( Michinov and Michinov, 2020 ; Tang et al, 2020 ; Elisondo, 2021 ; Hofreiter et al, 2021 ; Orkibi, 2021 ).…”
Section: Introductionmentioning
confidence: 99%